2019
DOI: 10.1016/j.bbmt.2019.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Outcomes of Primary Poor Graft Function after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a curative therapy for both malignant and nonmalignant hematologic disorders. However, primary poor graft function (PGF) is a serious early complication of allo-HSCT that leads to a poor outcome. Little is known about the characteristics, incidence, and risk factors of primary PGF occurring after allo-HSCT. Here we performed a 1:4 ratio nested case-control study in 830 patients who underwent allo-HSCT between April 2013 and November 2018 at our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 47 publications
(40 reference statements)
1
54
2
5
Order By: Relevance
“…A recent study, identified the SF level >2000 ng/ml as an independent risk factor for primary PGF (OR = 4.147; 95% CI: 1.452–11.845; p = 0.008), and the patients of SF level >2000 ng/ml had a poor 1-year overall survival. 3 …”
Section: Risk Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study, identified the SF level >2000 ng/ml as an independent risk factor for primary PGF (OR = 4.147; 95% CI: 1.452–11.845; p = 0.008), and the patients of SF level >2000 ng/ml had a poor 1-year overall survival. 3 …”
Section: Risk Factorsmentioning
confidence: 99%
“…Splenomegaly is reportedly another risk factor of primary PGF, 3 , 20 , 21 although the underlying diseases are heterogeneous. The possible mechanism might be that enlarged spleen could trap and destroy hematopoietic cells.…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations